Transcriptome Analysis of Immune Receptor Activation and Energy Metabolism Reduction as the Underlying Mechanisms in Interleukin-6-Induced Skeletal Muscle Atrophy - Sun, Hualin; Sun, Junjie; Li, Ming; Qian, Lei; Zhang, Lilei; Huang, Ziwei; Shen, Yuntian; Law, Betty Yuen-Kwan; Liu, Liang; Gu, Xiaosong (Frontiers in Immunology, 2021)
Background: Inflammation may trigger skeletal muscle atrophy induced by cancer cachexia. As a pro-inflammatory factor, interleukin-6 may cause skeletal muscle atrophy, but the underlying molecular mechanisms have not been explored. Methods: In this experimental study, we used adult male ICR mice, weighing 25±2 g, and the continuous infusion of interleukin-6 into the tibialis anterior muscle to construct a skeletal muscle atrophy model (experimental group). A control group received a saline infusion. RNA-sequencing was used to analyze the differentially expressed genes in tissue samples after one and three days. Gene Ontology and the Kyoto Encyclopedia of Genes and Genomes analysis were applied to define the function of these genes, and protein-protein interaction analysis was performed to identify potential transcription factors. Fluorescence microscopy was used to determine the muscle fiber cross-sectional area after 14 days. Results: Continuous infusion of interleukin-6 for 14 days caused significant muscle atrophy. RNA-sequencing found 359 differentially expressed genes in the 1- and 3-day tissue samples and 1748 differentially expressed genes only in the 3-day samples. Functional analysis showed that the differentially expressed genes found in both the 1- and 3-day samples were associated with immune receptor activation, whereas the differentially expressed genes found only in the 3-day sample were associated with reduced energy metabolism. The expression of multiple genes in the oxidative phosphorylation and tricarboxylic acid cycle pathways was down-regulated. Furthermore, differentially expressed transcription factors were identified, and their interaction with interleukin-6 and the differentially expressed genes was predicted, which indicated that STAT3, NF-κB, TP53 and MyoG may play an important role in the process of interleukin-6-induced muscle atrophy. Conclusions: This study found that interleukin-6 caused skeletal muscle atrophy through immune receptor activation and a reduction of the energy metabolism. Several transcription factors downstream of IL-6 have the potential to become new regulators of skeletal muscle atrophy. This study not only enriches the molecular regulation mechanism of muscle atrophy, but also provides a potential target for targeted therapy of muscle atrophy.